BUBUK KECOMBRANG (Nicolaia speciosa) SEBAGAI PENGAWET ALAMI PADA BAKSO IKAN TENGGIRI - Rifda Naufaalin; Herastuti Sri Sukmini (AGRICOLA, 2012)
Kecombrang’s stem in addition is to flavor and to get efficacious medicine, it also potential as antimicrobials. Kecombrang’s stem has chemical component such as alkaloids, saponins, flavonoids, phenolic, triterpenoid, steroids and glycosides. This research aims to study the influence of addition of kecombrang’s stem powderfrom inside apartas quality of mackerel meatballs. The quality is about microbial, chemical, sensory and the shelf life at room temperature.This research used a Randomized Block Design (RBD) consisting of 16 treatment combinations and twice repeated. The factors examined was the concentration of kecombrang’s stem powderfrom inside apart (0%; 1%; 2%; 3%) and the mackerel meatballs shelf life at room temperature (0day; 1day; 2 days; 3 days). The results are showed that an increase of the concentration (K) could reduce the sensory quality of the mackerel fish meatballs (as taste, texture, color, and fondness value), but was able to improve the quality of chemically and microbial through a decrease in pH values, Formolvalue, total bacteria, total yeasts and molds. Increasing a storage time (L) could reduce the quality of chemically and microbialof mackerel meatballs asreducing the pH value and increasing the formol value, total microbas, totalbacteria, total mold and yeast. The interaction of kecombrang’s stem powderfrom inside apart and the storage time of mackerel meatballs (K x L) could increase the total bacteria. The optimal concentration of kecombrang’s stem powder from inside apart is up to 2%.